Student and Teacher Experiences with Technology Integration in Reading Comprehension Instruction An Action Research Project - Floyd, Susan A. (My University, 2004)
Forty-four fifth-grade students in two intact classes participated in this action research study to examine student and teacher experiences with and without technology provided with the new Harcourt Trophies Distant Voyages Reading Series. The unit of study was reading comprehension skills such as identifying the main idea, recognizing details in a story, drawing conclusions, and summarizing. Measurement instruments included a pretest and posttest, surveys of student and teacher perceptions, and a classroom observation tool. Findings suggest that there were no differences in experiences between the two groups of students and between the two teachers. The total population technology group had slightly higher student achievement gains; among the at-risk students in the study, the technology group also had higher overall gains than the traditional group. These results will assist teachers and administrators with decisions about future use of the technology accompanying the series.
Keywords: Student and Teacher Experiences With and Without Technology